Moisture sorption isotherm modelling and thermodynamic functions of White Maize Ogi enriched with Drumstick (Moringa oleifera) seeds - Oladeji, Oluwatoyin Ajoke; Taiwo, Kehinde Adekunbi; Akanbi, Charles Taiwo (Asia Pacific Journal of Sustainable Agriculture, Food and Energy, 2024)
The study predicted the behaviour of enriched white maize ogi during storage at different temperature and; evaluate thermodynamic functions and fitness of experimental data into sorption models. Moisture sorption isotherm of sample products was determined for different water activities, aw, (0.1-0.8) at room temperature RT, (28±2), 35 and 40 oC using gravimetric method. The experimental data was fitted into four models (GAB, BET, Hasley and Oswin), fitness of the models assessed statistically by calculating coefficient of determination (r2), root mean square (RMS), and mean relative percent deviation modulus (E) and thermodynamics properties determined using Clausius-Clapeyron equation. Results showed that equilibrium moisture content of the product increased with increasing water activity, showing type II sorption isotherm, and decrease with increase in temperature at the same water activity. Statistical parameters revealed that GAB and Oswin models had better fit (r2 > 97%, E < 10%) for the experimental data than other models. Monolayer moisture contents, Mo, energy requirement and spontaneity of moisture sorption behaviour of Moringa oleifera seeds enriched maize products (Ogi-Moringa) were affected by method of incorporation of Moringa oleifera seed during processing. Sample with fermented Moringa oleifera seed had higher optimum keeping moisture content (3.928-7.33) as presented by Mo and require greater energy, to remove water molecules than required for the other sample.